Circular economy and it’s situation in Mexico - Córdova Preciado, Mónica L. (Posgrados de la División de Ciencias Económica Administrativas, 2021)
Derived from environmental damage as a consequence of the excessive use of raw materials and high consumer demand, it is necessary to seek alternatives that help implement a circular economy model, which implies the use of resources and therefore, the reduction of waste and thus evolve from the linear model. However, it is vital to understand the meaning of this concept and thus find strategies to implement it. In this context, the objective of this study was to conduct a literature review on the concept of circular economy and its situation in Mexico. As a result, Mexico is starting out on issues of sustainability and circular economy, which is why it is necessary to develop an action plan where organizations, government and society are committed to transformation.